The Impact of GDP Growth and Inflation on Corporate Revenue Growth: Evidence from listed companies in China - Li Guanlong (SHS Web of Conferences)
This study examines the impact of GDP growth rate and inflation rate on the revenue growth of nine major listed companies (e.g., Alibaba, Pinduoduo, etc.) in China from 2015 to 2023 through multiple regression analysis. It is found that GDP growth rate is significantly and positively related to firms’ revenue growth, while the effect of inflation rate is not statistically significant. GDP growth rate reflects the overall performance of economic activities and is an important predictor of firms’ revenue growth, whereas China’s inflation rate has been relatively stable during the study period, and therefore has a weak predictive effect on revenue growth. The theoretical contribution of this study is to reveal the impact of macroeconomic factors on firms’ financial performance, especially in the context of stable inflation rates. The practical implication is to help Chinese firms and investors understand the impact of macroeconomic indicators on firm performance, so that they can formulate more effective business and investment strategies to cope with market changes and minimize risks during periods of economic volatility.